Ultrabroad spectral response and excellent SERS performance of PbS-assisted Au/PbS/Au nanostars. Issue 47 (22nd November 2022) - Feng, Jing-Ru; Zhao, Zhi-Rui; Xiong, Zhong-Long; Kang, Hao-Sen; Ding, Si-Jing; Ma, Liang; Zhou, Li
Abstract : We successfully prepared Au/PbS/Au nanostars with adjustable spine length. The SERS results show that the Au/PbS/Au nanostars (long) have the strongest Raman signal. Abstract : Noble metal nanomaterials have many excellent optical properties due to localized surface plasmon resonance induced by external electric and magnetic fields. The plasmon-enhanced optical properties of nanomaterials can be controlled by changing their shapes or compositions. Here, we use a gentle approach to synthesize Au/PbS/Au nanostars with multiple tips and explore the surface-enhanced Raman scattering (SERS) activity, the second harmonic generation (SHG), and photocatalytic performance. The Au/PbS/Au nanostars have ultrabroad spectral responses and significantly enhanced local electric fields near the sharp tips. The size and tip length of the Au/PbS/Au nanostars can be adjusted by changing the amount of HAuCl4 . The Au/PbS/Au nanostars exhibit largely enhanced SERS activity and photocatalytic degradation efficiency compared with the Au bipyramids and the Au BPs@PbS nanocrystals. In addition, the SHG of Au/PbS/Au nanostars is also significantly enhanced due to asymmetry and local field enhancement. This research shows potential in many applications ranging from photophysics to photochemistry.